Self-esteem of patients with coronary artery disease - Pompeo, Daniele Alcalá; Eid, Letícia Palota; Carvalho, Isabela Gonzales; Bertolli, Eduarda dos Santos; Oliveira, Natalia Serafim de (Rev Rene, 2018)
Objective: to evaluate the self-esteem of individuals with coronary artery disease. Methods:this is a cross-sectional study, carried out with 77 participants. The instruments used were Hospital Anxiety and Depression Scale and Rosenberg Self-esteem Scale. Results: most of the participants had moderate self-esteem, 48 (62.3%), followed by a low self-esteem, 29 (37.7%), being influenced by the variables gender (p=0.040), education level (p=0.009), anxious symptoms (p=0.010) and depressive (p=0.030). Conclusion: patients with coronary artery disease presented medium and low self-esteem scores. Higher levels of self-esteem were associated with females, higher education level and the presence of anxiety and depression symptoms.